ＩＶメロキシカムにより血小板機能異常症の対象を治療する方法 (2022)
本開示は、それを必要とする第一の対象において痛みを治療する方法であって、血小板機能異常症の第一の対象にメロキシカムを投与することを含む方法を提供する。ある実施態様においては、メロキシカムの投与前に第一の対象から単離される血小板の閉塞時間は、血小板機能異常症でない以外のその他の条件は同様の対象から単離される血小板の閉塞時間よりも延長されている。ある実施態様においては、メロキシカムの投与後に第一の対象から単離される血小板の閉塞時間は、メロキシカムの投与前に第一の対象から単離される血小板の閉塞時間に匹敵する。 The disclosure provides methods of treating pain in a first subject in need thereof, comprising administering meloxicam to the first subject, wherein the first subject has a platelet dysfunction. In some embodiments, a closure time of platelets isolated from the first subject before administration of meloxicam is more prolonged than a closure time of platelets isolated from an otherwise similar subject without platelet dysfunction. In some embodiments, the closure time of platelets isolated from the first subject after administration of meloxicam is comparable to a closure time of platelets isolated from the first subject before administration of meloxicam.